Понтийские монеты из пантикапейского храма в антах - Зинько, В.Н. (Материалы по археологии, истории и этнографии Таврии, 2000)
При охранных раскопках в северо-западной части античного городища Пантикапей были выявлены остатки культового комплекса. Этот участок города на северном склоне горы Митридат в античную эпоху имел террасную планировку. In the northwestern part of ancient Pantikapaion the remnants of a cult complex dating back to the end of the 3rd century BC were revealed. Judging by the fragments of architectural details the building used to be a temple in the ants of Doric order. The building was destroyed by the fire in the first third of the 1st century BC. In this article the autor characterizes the four Pontus coins found during the excavation of the temple. The earliest coin -a copper tetrahalk of Amisus; it is dated back to 100-85 BC. The two similar copper tetrahalks of Sinope are dated back to 80-70 BC. The latest Pontus coin - a good stater of Mithradates VI Eupatoros - is of the greatest interest Judging by the inscription on the coin it was minted in 69-68 BC. However, it is considered that minting gold staters with the portrait of the king was stopped in the mid-80s of the 1st BC and then only silver tetradrachmas with his portrait were put into circulation. The stater with such late dating is unique Mithradates staters had not been found on the territory of the Bosporos Kingdom.